Fractionation and anti-inflammatory effects of polyphenol-enriched extracts from apple pomace (Bangladesh Journal of Pharmacology, 2012)
Bioactive polyphenols are the predominant ingredients in apple pomace, an agro-industrial byproduct in apple juice processing. The present work focused on fractionation of ethanol extract of apple pomace using macroporous absorbent resin chromatography and HPLC analysis of all fractions recovered from polyphenol-enriched extract and their inhibitory effects on cyclooxygenase-2 (COX-2) expression in lipo-polysaccharides (LPS) -induced mouse RAW 264.7 cell line. Six fractions API-VI were achieved through fractionation eluting with aqueous alcohol. HPLC analysis indicated that APIII eluted by 40% ethanol had the highest content of total phenolics, which was 148.1 ± 3.11 mg gallic acid equivalents per 100 g of dry apple pomace. Anti-inflammatory assays showed that APIII had the strongest activity against COX-2 expression at 5 ?g mL-1 and procyanidin B2 and quercetin exhibited positive correlation with their anti-inflammatory effects. Our data suggested that phenolics could be prepared from apple pomace and applied in the management of inflammatory diseases.